Taxpayer Compliance: Determinants of Tax Administration and Tax Volunteer Moderation - Imam Hadiwibowo; Ali Jufri; Trizka Alyaa Herdina; Faldi Ibrahim (West Science Business and Management, 2023)
Taxes are the biggest contributor to the current state budget. The government, through the Directorate General of Taxes, tries to always optimize revenue from the tax sector by seeking changes in various aspects towards a better direction. In order to increase the level of taxpayer compliance, the Director General of Taxes has attempted to create innovation by implementing tax modernization. The aim of tax modernization itself is to optimize revenue, implement a reliable administrative system, utilize information technology, form a good image and trust from the public and tax modernization is also expected to be able to increase personal taxpayer compliance in completing their obligations when registering, reporting, making deposits. and pay taxes. The aim of this research is to find out whether the application of NIK as NPWP, e-Filling, e-Form and e-Billing affects individual taxpayer compliance and to find out whether the role of tax volunteers can moderate the application of NIK as NPWP, e-Filling, e-Form and e-Billing on individual taxpayer compliance